In-situ enrichment and application of heterotrophic nitrification-aerobic denitrification bacteria in membrane aerated biofilm reactor. (December 2022) - Lan, Meichao; Kang, Yongqiang; Wang, Jixiao; Li, Ming; Zhang, Peng; Zhang, Pengyun; Li, Baoan
Abstract: In order to reduce the resource and energy consumption of traditional biological nitrogen removal (BNR) process, heterotrophic nitrification-aerobic denitrification (HN-AD) bacteria was in situ enriched in membrane aerated biofilm reactor (MABR) by inoculating conventional activated sludge. Contaminants removal performance, EPS composition and microbial community were explored. The results indicated that the average removal efficiency of COD and TN under optimal condition reached 84.13% and 91.54%, respectively, which demonstrated that the reactor possessed excellent contaminants removal capacity. EPS analysis suggested that abundant protein especially tryptophan protein-like substance played a vital role in maintaining the microbial stability of biofilms. Multiple HN-AD genera, mainly Paracoccus, were detected with the highest relative abundance of 54.70%, which confirmed the successful enrichment of the HN-AD bacteria. Conventional nitrifiers and denitrifiers also thrived in biofilm, which demonstrated the synergistic nitrogen removal of multiple microorganisms. This study provided important insights into application of HN-AD bacteria and synergistic nitrogen removal in BNR system. Graphical abstract: Image 1 Highlights: HN-AD bacteria were in situ enriched in a conventional MABR. The highest average ORE and TNRE reached 84.13% and 91.54%, respectively. Tryptophan protein-like substance was the predominant component in EPS. The highest relative abundance of HN-AD genera in biofilm reached 54.70%. Synergistic nitrogen removal occurred in the reactor.